Evaluation of crop water consumption using water footprint for sustainable water management in Tehran, Iran - Kalvani, Somayeh Rezaei (2019)
The escalation in water use around the world has become a concern. Recently, Iran is facing high water crisis due to unsustainable water management. The objectives of this study are to evaluate the surface and ground water footprints for all crops in Tehran from 2008 to 2015, to estimate the shortage of surface and groundwater in agricultural sector between 2014 and 2015, as well as to assess the variability of per capita Water Footprint (WF) from 2008 to 2015. The evaluation of the blue and green WFs is done according to the WF approach. The evapotranspiration has been evaluated using CROPWAT software. For the first time, the Geographic Information System (GIS) data and fieldwork are utilized to determine ground and surface WFs. The sum of the green and blue WF of crop production had increased from 986,857,963 m3/year (2008) to 1,097,738,205.2 m3/year (2015). Besides that, it is indicated that the groundwater is under severe stress (agricultural groundwater scarcity accounted 0.95) for the production of crops alongside moderate surface water stress (agricultural surface water stress accounted 0.4). Although Tehran is facing a serious issue on the groundwater stress, the additional production of agricultural crops (e.g. pear, peach and cherry) is traded to other areas, with extensive scale of production. However, external WF had the largest contribution in WF of crops consumption, accounting 90% of total WF. Tehran province lost 26.691 million cubic meter (MCM) of blue water because of the exportation of pear, peach and cherry. The largest per capita WF is allocated to the wheat and the rice consumptions, accounting 189 and 49 m3/cap/year respectively. Tehran can take advantage of importing water intensive crops (wheat and rice). 2.88 billion m3 of water resources in Tehran was saved due to the international and inter provisional crop trade (2008–2015). The production of cereal crops (wheat, barley and maize) consumed 283.776 MCM and 152.460 MCM of groundwater and surface water resources respectively, accounting for 52% of agricultural blue WF (2008-2015). It is recommended to reduce cereal crops production in Tehran province since the production of cereal crops consumed half of the total water withdrawal in the agricultural sector. Moreover, the production of fruits (cherry, pear and peach) for exporting should be reduced. Residents of Tehran consumed a large volume of wheat in their diet, twice larger compared with global average. Therefore, increasing food security by changing food consumption pattern at regional scale is recommended. Reduction in consumption of wheat or replacing it with other crops is suggested. Hence, it would be beneficial to account WF of various dietary changes in future WF evaluation. Wheat should be produced in areas of Iran with humid and semiarid climates because the production of wheat in a humid climate consumes the largest amount of green water and a lower amount of blue water resources. This research reveals that it is crucial to have suitable water management to decline water scarcity stem from agricultural division in the future. Additionally, reducing water footprint, increasing productivity, and appropriate agricultural water management are recommended. Apart from that, agricultural groundwater and surface water scarcity indices are more appropriate compared to the existing indicators because these indicators are able to reveal environmental impact of crop production and assist stakeholders in the assessment of groundwater and surface water management policies.